Transforming Character Education through Islamic Philosophy in the Modern Era - Harahap, Nikmah Royani; Gajah, Nina Badriah; Harahap, Hotni Sari; Jannah, Fathul (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This conceptual study examines how Islamic philosophy provides a transformative ethical foundation for moral education by synthesizing the key ideas of classical thinkers such as Al-Farabi, Al-Ghazali, and Ibn Miskawayh. In response to the global moral crisis and the limitations of behaviorist approaches in education, the study critically explores four interrelated concepts ʿaql (reason), tazkiyah (moral purification), adab (refined conduct), and hikmah (wisdom) as philosophical frameworks for character formation. Using a qualitative conceptual research design, the study employs library research and thematic content analysis to reinterpret classical Islamic texts and contemporary academic literature. The findings reveal that reason serves as the foundation for ethical judgment and autonomy, moral purification strengthens internal discipline and sincerity, refined conduct represents the external expression of virtue in social life, and wisdom integrates intellectual, ethical, and spiritual maturity. Practically, these principles can guide educators in developing value-based curricula, reflective learning, and ethical role modeling in both Islamic and pluralistic educational contexts. Collectively, the study proposes an Islamic philosophical framework for rehumanizing moral education and bridging the gap between knowledge and virtue in contemporary learning environments.